STUDY OF MOSQUITOES FROM THE PERSPECTIVE OF SCIENCE AND RELIGION AS A SOURCE OF EDUCATIONAL VALUES - Iswandi; Syofrianisda; Lutfiyani; Yulda Dina Septiana (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Studies on mosquitoes have generally focused on biological and health aspects, particularly their role as disease vectors, thereby overlooking the educational and reflective dimensions of this object of study. However, from a holistic educational perspective, natural phenomena, including small organisms such as mosquitoes, can be interpreted as sources of values and learning. This study aims to identify and analyze the educational values embedded in studies on mosquitoes through a Systematic Literature Review (SLR) approach. The research method involved searching for relevant academic articles and scholarly sources published within a specific time frame through scientific databases, which were then selected using clearly defined inclusion and exclusion criteria. The selected data were analyzed using thematic analysis to identify patterns and categories of educational values. The results indicate that studies on mosquitoes contain several key educational values, namely intellectual humility, ecological responsibility, perseverance and adaptability, spiritual awareness and monotheism, as well as scientific ethics and empathy. These findings affirm that mosquitoes not only have scientific significance but are also relevant as pedagogical media in character education and value-based learning. This study concludes that the SLR approach is effective in uncovering the educational value dimensions of scientific literature and opens opportunities for integrating scientific inquiry with humanistic and spiritual values in educational practice.